Analisis Preferensi Konsumen dan Review Influencer @Fujiiian terhadap Keputusan Pembelian di Social Commerce TikTok - Vita Aulia Malik; Novie Susanti Suseno; Resty Mustika Pratiwi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The development of social commerce, especially on the TikTok platform, has changed the way consumers make purchasing decisions. In addition to being a platform for entertainment, TikTok is a powerful tool for marketing thanks to interactive elements like live broadcasts and the yellow shopping. Many merchants market their products on TikTok. This study aims to analyze how consumer preferences and influencer reviews on the @Fujiiian account influence purchasing decisions on TikTok social commerce. The research method used is quantitative descriptive with data collection techniques through surveys of 40 respondents and statistical analysis using chi-square and attitude measurement scales. The results of the study show that consumer preferences, such as reviews, ratings, and comments, have a significant influence on the level of trust and purchasing decisions. Consumers tend to buy products with positive reviews and high ratings. In addition, influencer reviews play an important role in building product credibility and increasing consumer interaction. Influencers with a large number of followers and high levels of engagement are able to increase product appeal through interesting and informative content. TikTok's social commerce features, such as live broadcasts and direct links to products, also facilitate the purchasing process. This study provides an important contribution to understanding the formation of consumer behavior on social commerce platforms, as well as being a strategic reference for business actors in utilizing influencers and consumer preferences to increase the effectiveness of digital marketing.